PCG and ECG Portable Acquisition System - Silva, José Mário Meira da (2022)
Heart disease is the leading cause of death in the world, victimizing human beings in all age groups and from different geographic areas. Through the evolution of auscultation technology, the identification and analysis of heartbeats make it possible to prevent and treat heart pathologies with greater success. In this project, a portable, low-power system was developed that allows the acquisition of heart sound signals simultaneously in four different auscultation zones, as well as the acquisition of an electrical signal, subsequently conditioning and processing the different signals. The system also allows the transmission of signals in real-time via Bluetooth Low Energy to a mobile device where they can be recorded for future analysis. The portable system records four phonocardiographs located at four auscultation areas, namely the aortic valve, the mitral valve, the pulmonary valve and the tricuspid valve. These sound signals are converted to analog electrical signals that will be amplified, filtered and converted into digital signals. There is also a two-electrode electrocardiograph in this system, which is also amplified and filtered before being converted to a digital signal and transmitted via wireless communication. The entire system is powered by a battery with a charge voltage of 4.2 V, which allows it to be charged through the USB interface.